2018
DOI: 10.3233/xst-18389
|View full text |Cite
|
Sign up to set email alerts
|

A study on the characteristics of mobile X-ray device using supercapacitor as internal power

Abstract: Mobile X-ray device is widely employed because it is useful for diagnosis in patients having mobility difficulties and in medical emergencies. As various devices for X-ray generation have continued to be developed, X-ray devices can now be used more safely and effectively. However, mobile X-ray devices generate relatively low X-ray doses due to the limitation of the power input. Therefore, the use of mobile X-ray devices is limited to thin parts of body. In this study, a new device was designed in order to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[ 25–27 ] Calculation results indicated that the borophene is a nanometer material, which is mechanically burly, soft, and tough, [ 28 ] highlighting the potential application in sensors, [ 29 ] DNA sequencing, [ 30 ] nanotechnologies, [ 31 ] Li‐ion and Na‐ion batteries, [ 32 ] and medical radiology. [ 33,34 ] Compared with prosperous developments of theoretical simulations, experimental progress of borophene was rare until recent years. Chemical vapor deposition (CVD) [ 35,36 ] and molecular beam epitaxy (MBE) [ 37,38 ] have demonstrated growth of 2D borophene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–27 ] Calculation results indicated that the borophene is a nanometer material, which is mechanically burly, soft, and tough, [ 28 ] highlighting the potential application in sensors, [ 29 ] DNA sequencing, [ 30 ] nanotechnologies, [ 31 ] Li‐ion and Na‐ion batteries, [ 32 ] and medical radiology. [ 33,34 ] Compared with prosperous developments of theoretical simulations, experimental progress of borophene was rare until recent years. Chemical vapor deposition (CVD) [ 35,36 ] and molecular beam epitaxy (MBE) [ 37,38 ] have demonstrated growth of 2D borophene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile radiography is a common model of such appliances. 196 Likewise, borophene can even function as a supercapacitor with relevant attributes empowering potential portable tools. 197 By adjusting the potential on X-ray tubes, tuneable power can be used to produce X-rays via borophenebased devices for better diagnostics.…”
Section: Borophene For Developing High-performance Medical Equipmentmentioning
confidence: 99%
“…Borophene could increase the performances or prolong the lifecycles of biomedical devices, both in nano-strips and integrated with other metals. One example of a ready-to-use device is the portable radiograph [29]. X-rays are produced via a complex process requiring energy.…”
Section: Borophene In Radiology For Medical Applicationsmentioning
confidence: 99%